HE EFFECT OF PROBLEM BASED LEARNING MODEL AND PROBLEM POSING TO STUDENT PROBLEM SOLVING OF MATHEMATICS ABILITY - Astri Wuryani; Intan Sari Rufiana (EDUPEDIA, 2018)
his research aims to: (1) find out whether is there the influence of problem based learning toward the student problem solving of mathematics ability at seventh grade of SMP N 1 Balong, (2) find out whether is there the influence of problem posing toward the student problem solving of mathematics ability at seventh grade of SMP N 1 Balong, and (3) find out whether the difference of problem solving ability between the students get problem based learning with the students get problem posing learning. The research design was pre-experimental with the population covering all seventh grade students of SMP N I Balong consisting of eight classes. Classes VII G and VII H were selected as the sample. The selection of sample class used purposive sampling technique. From eigth classes, Class VII G was treated problem based learning and class VII H was treated problem posing. Data collection technique was test ability to solve mathematical problems. Data analysis technique was used paired sample t-test and t sample independent test.The results on 0.05 significant level showed that the problem based learning has an influence to the students’ mathematics problem solving ability. Similarly, problem posing learning has an effect to the students’ problem solving ability of mathematics. When reviewed from the both of problem solving ability of mathematics model, problem based learning isn’t different with problem posing.